The Use of IL-1 Receptor Antagonist (Anakinra) in Idiopathic Recurrent Pericarditis: A Narrative Review. (31st January 2016) - Baskar, Shankar; Klein, Allan L.; Zeft, Andrew
Abstract : Recurrent pericarditis is a complication of acute pericarditis in 20–30% of the patients and is usually idiopathic in nature. The underlying pathogenesis of this condition remains unclear, although immune-mediated mechanisms seem likely. A subgroup of these patients with refractory symptoms can be challenging to manage, and multiple immunosuppressive medications have been used without consistent benefit. Anakinra, an interleukin-1 receptor antagonist, has been used in treatment of rheumatoid arthritis and autoinflammatory syndromes. Preliminary evidence suggests that anakinra could be a promising therapy for idiopathic recurrent pericarditis. In this narrative review, we summarize the current understanding of the etiopathogenesis of idiopathic recurrent pericarditis, mechanism of action of anakinra, and the preliminary evidence, supporting the use of anakinra in pericarditis.